al-Tajribah al-Miṣriyyah (The Egyptian Experience) - Muhd Abdul Mateen Hisham (Universitas Islam Internasional Indonesia (UIII), 2026)
Jum‘ah, Ali. al-Tajribah al-Miṣriyyah (The Egyptian Experience). Cairo: Nahḍat Miṣr li-al-Ṭibā‘ah wa-al-Nashr wa-al-Tawzī‘, 2008. “The world we live in has changed,” emphasised Dr Ali Gomaa. Yet many continue to grapple with how to uphold their identities in a rapidly evolving modern world. In recent decades, various calls have emerged for the establishment of an Islamic state or the formal implementation of the Shariah (Islamic law). In Malaysia, the Malaysian Islamic Party (PAS) has remained particularly vocal, seeking to formally enact elements of Shariah through the criminal code in place of existing state ‘secular’ laws.[1] This political endeavour, which some have coined as the Shariatisation of the political discourse, has continued to rally support, particularly from religious conservatives, and bolster the party’s electoral presence. The community’s response to this initiative reflects how Shariah is perceived, especially in relation to the secular state. [1] Syaza Shukri & Norshahril Saat, Sharia versus Shariatisation in Malaysia: Which One Will Triumph?, Fulcrum: Analysis on Southeast Asia, ISEAS (Yusof Ishak Institute), 2024 https://fulcrum.sg/sharia-versus-shariatisation-in-malaysia-which-one-will-triumph/